2023
DOI: 10.2147/idr.s395382
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Targeted Treatment and Mass Drug Administration Delivery Strategies on the Prevalence and Intensity of Schistosomiasis in School Aged Children in Africa: A Systematic Review

Abstract: Schistosomiasis is a public health problem in more than 78 countries in the world. The disease is most prevalent among children than adults due to their high exposure to infectious water sources. Various interventions such as mass drug administration (MDA), snail control, safe water provision and health education have been implemented independently or jointly to control, reduce and ultimately eliminate Schistosomiasis. This scoping review focused on studies reporting the impact of different delivery strategies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
(164 reference statements)
0
3
0
Order By: Relevance
“…haematobium and S . mansoni [ 4 ]. The symptoms of the acute form of the infection include Katayama fever, rash, diarrhoea, nausea, and stomach pains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…haematobium and S . mansoni [ 4 ]. The symptoms of the acute form of the infection include Katayama fever, rash, diarrhoea, nausea, and stomach pains.…”
Section: Introductionmentioning
confidence: 99%
“…WHO recommends preventive chemotherapy and test-and-treat approaches for PSAC and SAC, along with health education, improved sanitation, and water access, however, no studies have been done to assess the collective effects of the schistosomiasis control programs in sub-Saharan Africa on the paediatric population [ 11 ]. Systematic reviews done in the field have reported on the impact of targeted treatment and mass drug administration delivery strategies, but no further exploration was done on different intervention strategies [ 4 ]. Sokolow et al [2016] evaluated the effectiveness of different schistosomiasis control strategies used globally over the 20th century.…”
Section: Introductionmentioning
confidence: 99%
“…In a study examining the first mass drug administration (MDA) campaign for schistosomiasis in a highly urbanized state in Nigeria, Olamiju et al focused on implementation strategies and highlighted the associated challenges. The implementation of public health MDA campaigns for schistosomiasis is crucial to achieving widespread coverage of preventive treatment, reducing transmission rates, and ultimately controlling the burden of disease in endemic regions ( Chanhanga et al, 2023 ). However, MDA plans must be efficiently designed to achieve their goals.…”
mentioning
confidence: 99%